Relationship Between Interleukin 6 (IL-6) and Organ Damage Based on SLICCDamage Index -SDI Score in Systemic Lupus Erythematosus Patients - Yesanopa Sianturi (Indonesian Rheumatology Associantion, 2024)
Background: Systemic Lupus Erythematosus (SLE) is a heterogeneousand complex chronic autoimmune disease. Interleukin 6 (IL-6) is acytokine known to be elevated in people with SLE. This research wasconducted to determine the relationship between IL-6 levels and organdamage based on the SLICC Damage Index-SDI Score in SLE patients.Method: The study was a retrospective cross-sectional study involving67 SLE patients conducted based on the SLICC 2012/ACR EULAR2019 criteria at least 6 months prior to their inclusion. They werepatients treated at the Rheumatology Clinic of Adam Malik GeneralHospital in Medan from June to August 2023, who met the inclusionand exclusion criteria. Organ damage assessment was done using theSLICC Damage Index (SDI) score, while disease activity degree wasmeasured using the SLE Disease Activity Index (SLEDAI-2K) scoringsystem. Results: 94 % subject were women with a median SLEDAI-2Kscore of 6 (10 – 16) where the moderate degree of activity was themajority in this study (41.8%), followed by the mild degree (37.3%),severe (16, 4%), and remission (4.5%). The median IL-6 level was63.3932 pg/ml (8.88 – 5966.67) where a significant correlation wasfound between IL-6 levels and the SDI score (p=0.017) and the degreeof disease activity and the SDI score (P<0.001). Conclusion: Asignificant positive correlation was found between IL-6 levels and SDIscores in SLE patients (p=0.017).